PENGARUH STRUKTUR MODAL (DER), PROFITABILITAS (ROA) DAN UKURAN PERUSAHAAN (SIZE) TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL MODERASI KEPEMILIKAN MANAJERIAL (Studi Pada Perusahaan Manufaktur di BEI Tahun 2014-2018)â€ - Nugroho, Prihasantyo Siswo; Sumiyanti, Tri; Astuti, Ratna Puji (JAB (Jurnal Akuntansi & Bisnis), 2019)
ABSTRACTÂ The company's value is reflected in the company's stock price which is reflected in the bargaining power of the stock. Corporate growth is one indicator or measurement of how a company develops or grows within a certain period (Purwohandoko, 2017). The variables in this study are dependent variables: Firm Value, independent variables: Capital Structure, Company Size, Profitability, moderating variables: Managerial Ownership. This study aims to analyze the effect of capital structure, firm size, profitability on firm value with managerial ownership as moderating. The population in this study were all companies listed on the IDX totaling 596 companies. This study specializes in manufacturing companies in the Indonesia Stock Exchange with the study period starting from 2014 to 2018. The sample that can be examined in this study amounted to 195 companies. Based on the Moderating Regression Analysis analysis, the capital structure does not affect on firm value, firm size has a positive effect on firm value, profitability has a positive effect the value of the company. Whereas the moderating variable of managerial ownership is not capable of modifying all variables of capital structure, firm size and profitability of firm value.Keyword : Capital Structure, Company Size, Profitabilitas, Managerial Ownership, Firm Value